Manna from heaven': does the presence of central banks make technical analysis profitable? - Smita Roy Trivedi (European Journal of Economics and Economic Policies: Intervention (EJEEP), 2021)
Profitability of technical-analysis strategies has been explained with reference to central-bank intervention in markets (Neely 1998; LeBaron 1999; Saacke 2002). I argue that central-bank intervention is a market shock which leads to a generation of trends, making technical analysis profitable. Looking at empirical evidence from the Indian foreign-exchange market, I find returns calculated for the entire period are consistently and substantially higher than when intervention periods are removed. Thirteen out of the 15 strategies demonstrate higher returns with intervention periods included, compared to without intervention periods. The Kolmogorov–Smirnov sample tests show statistically significant differences in the returns between the entire period and the without-intervention period for four strategies, which is confirmed by bootstrap estimation. The paper contributes first by including actual trading strategies in the empirical testing of profitability of technical analysis and second by emphasizing the efficacy of technical analysis rather than the action of the central bank itself in explaining profitability, in a departure from the existing literature.
Keywords: E44; E58; F31; 330; central bank intervention; technical analysis; profitability of trading strategies; Reserve Bank of India